Mediating Effect of Environmental Attitude on Green Product Purchase Intention in Indonesia - Eksa Kartika, Elta; Pradana, Mahir (The International Journal of Business Review (The Jobs Review), 2024)
This study aims to determine the relationship between green product quality and green brand image on green purchase intention mediated by environmental attitude. The method used is a quantitative method with purposive sampling type. The sample in this research is 400 respondents who are using  Love, Beauty and Planet products. The data analysis technique using descriptive analysis and Structural Equation Modelling (SEM). The results of this study shows that green product quality, green brand image, and environmental attitude has a significant influence on green purchase intention. The environmental attitude variable as a mediator has a significant influence in mediating the relationship between green product quality and green brand image on green purchase intention.